A short historical overview of plant opal studies: from discovery to modern applications - Pető, Ákos (JOURNAL OF LANDSCAPE ECOLOGY, 2009)
At the beginning of the 19th century, when pioneers of the microscopic world were delving deeper and deeper in the fascinating forms and phenomena of microscopic creatures, a German scholar, STRUVE was the first expert to report (1835) on phytoliths observed on slides prepared of living plant tissue. Paradoxically it happened a year earlier than the extraction of pollen grains from Quarternary sediments. Hundred and fifty years had to pass by – sixty-five years more as in the case of palinology – till phytolith research became an own discipline serving the goals of botany, paleoecology and environmental archaeology.
Keywords: phytolith; paleo- and archaeobotany; palaeopedology; palaeoecology; environmental archaeology; science history